STRATEGI PENINGKATAN PROFESIONALISME GURU MELALUI INSERVICE TRAINING EDUCATION - Ridho, Sholeh (Universitas Nurul Jadid, 2014)
To achieve the goal of education as established, education has any components that were interrelated with each other. These components consist of instrumental components and environmental components. In this case, the teacher is the part included in the instrumental parts. Therefore, a teacher professionalism associated with the effort to prepare a students to be human as a “ulul albab” and uplift the educational institutions that occupy, so that be believed by the public in relation to the achievements and excellence of input, process, output and the outcome. The magnitude of the responsibility of teachers alongside his personal and social responsibility is also in the learning process in an educational institution that serves as a mediator in the delivery of the material that is taught to students, henceforth be followed up by learners in real life, both in school and outside of school. Therefore, in order to improve the professionalism of teachers needed inservice training that is a powerful tool to make a changes to more advanced and effort the development skills of the teachers in learning process that leads to individual professionalism.